Inovasi Pendidikan Berbasis Green Pedagogy Sebagai Upaya Membangun Kecerdasan Ekologis Dalam Pembelajaran IPS - Utami, Lingga; Supriatna, Nana (Yayasan Perguruan Kampus, 2024)
This study aims to analyze green pedagogy as an educational innovation in social studies learning to build ecological intelligence in students. Green Pedagogy emerges as an innovative development in social studies education by integrating sustainability principles and environmental awareness. The research approach employed is qualitative, utilizing a library research method for data collection from books, journals, and other relevant literature. The results of the study indicate that the implementation of green pedagogy in social studies learning not only serves as a medium to enhance students’ environmental awareness but also promotes the creation of creative solutions to ecological problems. In its application to social studies learning, green pedagogy encourages students to better understand and appreciate nature through a holistic, interdisciplinary, and participatory learning approach. social studies education incorporating green pedagogy can lead to deeper social interactions and environmental awareness. The novelty of this research provides empirical evidence that the green pedagogy approach can shape students’ ecological intelligence to critically and sustainably respond to environmental challenges. Therefore, green pedagogy is recommended for adoption as an educational innovation aimed at broadly supporting sustainable development and ecological awareness as a shared responsibility.